Multifunctions Coins Saving Box (MCSB) / Mimi Amira Shafie, Siti Nur Atirah Ramli and Noor Ainul Husna Ismail - Shafie, Mimi Amira; Ramli, Siti Nur Atirah; Ismail, Noor Ainul Husna (2018)
The team development multi function box coin and application control use the multifunction coin saving box (MCSB). Multifunction coin saving box is smart saving box can used with the application. (MCSB) have many benefit for user such as able to control daily expenses and the (MCSB) fully safety. The application name is KETS. KETS is knowledge enjoyable technology saving. The multifunction coin saving box is smart saving box to encourage teenager to saving their money. Target market for multifunction coin box is 13 - 15 year old. The main function KETS is make teenager enjoy to saving .The KETS have game in the application, also can reminded user to saving. The application requires users to access WIFI if user want to use (MCSB) to connect with WIFI because the coin saving box can change the wallpaper of the material and user can search any wallpaper for the coin saving box.